2018
DOI: 10.1007/s13762-018-2099-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of surfactant-rich industrial wastewaters with concentrated sunlight: toward solar wastewater remediation

Abstract: We report here on a photo-Fenton process powered by concentrated sunlight applied for the treatment of surfactant-rich (5-20 g/L) industrial wastewaters. Degradation yields of 89% in 2 min in homogenous and 23% in 1 h for heterogenous conditions pave the way for the development of a low-cost/high-yield wastewater treatment process. Employed as a preliminary stage in wastewater treatment plants or as a small-scale stand-alone operated by small-medium enterprises, it could reduce the environmental and economic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Nevertheless, the increased use of these compounds in densely populated areas and/or the proximity to industrial complexes where the production of these detergents occurs may lead to the point release but with very high loads of these compounds into the environment. Kowalska et al ( 2005 ) reported concentrations of anionic surfactants exceeding 1500 mg·L −1 in effluents from the detergent production industry, while Orlandi et al ( 2019 ) reported values up to 780 mg·L −1 in wastewater effluents from a spa in India. The latter values, when compared to the HC 5 values derived here (remembering that 20% are already regarded as a threshold for effect), are thus considered of high environmental concern, highlighting here the need to provide more environmentally friendly variants as the aim of the presented work.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the increased use of these compounds in densely populated areas and/or the proximity to industrial complexes where the production of these detergents occurs may lead to the point release but with very high loads of these compounds into the environment. Kowalska et al ( 2005 ) reported concentrations of anionic surfactants exceeding 1500 mg·L −1 in effluents from the detergent production industry, while Orlandi et al ( 2019 ) reported values up to 780 mg·L −1 in wastewater effluents from a spa in India. The latter values, when compared to the HC 5 values derived here (remembering that 20% are already regarded as a threshold for effect), are thus considered of high environmental concern, highlighting here the need to provide more environmentally friendly variants as the aim of the presented work.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the drawback of difficulties of concentrating UV light (<400 nm), results evidenced a possible reasonable option if used with low costs catalysts to accelerate the degradation In solar wastewater purification, the selection of a PDC is motivated by specific needs. Being the most effective concentrators-reaching concentration ratios higher than 2000 suns-they can provide an advantage in cases where a very high photon density and/or thermal processes enhance pollutant degradation, for example, when the rapid abatement of a high content of pollutant is needed [54].…”
Section: Fresnel Solar Concentratorsmentioning
confidence: 99%
“…Surfactants are widely used in pulp-paper industries, detergents, oil recovery, household use, pharmaceuticals, emulsifying agents, textiles, disinfectants, cosmetics, paints, wetting agents and polymers, and so on. [2][3][4][5] Due to the high solubility of surfactants, they can be present in high concentrations in water and can cause biological and treating problems. Many of surfactants have been tested and found to be toxic to humans.…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports about adverse effects of surfactants on the environment, wildlife, and humans. [2,4] In addition to humans, surfactants are harmful to fish and plant life by causing foam in the rivers and reducing water quality. [3] Also, some surfactants can even increase antibiotic resistance in germs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation